Early life incidence of gastrointestinal and respiratory infections in children with gastroschisis: a cohort study - Bannister, Jessica; Szatkowski, Lisa; Sharkey, Don; Tan, Shin; Fiaschi, Linda; Ban, Lu (Lippincott, Williams & Wilkins, 2018)
Objectives: Survival in infants with gastroschisis is increasing although little is known about early childhood morbidity. In the context of a hypothesised link between the gastrointestinal (GI) tract and immune function, this study explores rates of GI and respiratory infections in children with gastroschisis. Methods: We conducted a population-based retrospective cohort study using data from the Health Improvement Network (THIN), a large database of UK primary care medical records. We identified children born from 1990 to 2013, and extracted follow-up data to their fifth birthday. We calculate incidence rates (IR) of GI and respiratory tract infections, overall and stratified by age, sex, socioeconomic status and gestational age at birth, and compared these between children with and without gastroschisis by calculating adjusted incidence rate ratios (aIRR). Results: Children with gastroschisis had a 65% higher IR of GI infection compared to children without (aIRR 1.65, 95% CI 1.37-1.99, p<0.001). Children with gastroschisis had a 27% higher IR of all respiratory tract infections (aIRR 1.27, 95% CI 1.12-1.44, p<0.001) and more than 2-fold increase in lower respiratory tract infections compared to children without the condition (aIRR 2.15, 95% CI 1.69-2.74, p<0.001). Conclusions: Children born with gastroschisis have a significantly higher incidence of GI and respiratory tract infections compared to children without gastroschisis. This association requires further investigations but could be related to the neonatal care they receive such as delayed eneteral feeding or frequent antibiotic courses altering the gut microbiome and developing immune system.